FOREIGNIZATION AND DOMESTICATION IN THE MINISTERIAL WEBSITE LOCALIZATION - Ely Hayati Nasution; Roswita Silalahi; Vivi Adryani Nasution (Universitas Bengkulu, 2019)
The translation is a representation of the effect of developing technology on language. Translated website or website localization with the easiness of accessibility is considered as the most efficient space for transferring the information nowadays. It certainly involves the appropriate translation strategies in order to provide reliable information required. This research aims to identify the translation strategy involved under foreignization and domestication reference in the official website localization of Ministry of Health of Republic of Indonesia, to find out the most dominant translation strategy used, and to analyze the reasons to what extent foreignization and domestication applied, by referring the classifications proposed by Venuti (2008). The source of data was taken from five (5) popular news along 2018 which were broken down into 191 data analyzed, consisting of 5 headlines in the form of phrases and sentences, contents totally written in 161 sentences, and 25 sub-contents in the form of words, phrases, clauses, and sentences. The research found that the translator used all eight (8) translation strategies under domestication and foreignization reference including literal translation, transliteration, borrowing, transference, transposition, omission, addition, and adaptation, simultaneously or separately. Literal translation becomes the most dominant translation strategy used and it can indicate that the website localization is translated into source text-oriented.